Benefits of Chia Seeds as a Functional Food for Cardiovascular Diseases Prevention: A Review - Jung Yeu Kim; Alexandra Amanda Ningtyas; Reynaldi Budiman W; Clarabelin Clarabelin; Willy Setiawan; Aurelia Faustine Wu; Anganjani Samaraswasdee Arya; Junaida Astina (Indonesian Journal of Life Sciences, 2024)
In order to increase the overall health while keeping the lifestyle, the interest of consuming lipid-based food or lipid-modifying foods are growing. Chia seed is an annual herbaceous plant that is rich in lipids (30–33%), carbohydrates (2–41%), dietary fiber (18–30%), and protein (15–25%). Chia seeds also contain high amounts of bioactive compounds, such as omega-3 fatty acids, antioxidants, and polyphenols to prevent some chronic diseases. Its rate of consumption has grown over the years due to its health benefits for chronic conditions such as obesity, cardiovascular disease, diabetes, and cancer. Some studies have been done to prove the benefits of consuming chia seeds. The aim of this paper is to review the morphology, composition, and benefits of chia seeds towards the prevention of cardiovascular diseases.